PENGARUH PEMBERIAN BERBAGAI JENIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KALE (Brasicca oleraccea var.acephala) - Sandra Dewi, Ferra Listya; Barokah, Umi (Agros Journal of Agriculture Science, 2024)
Kale is a leafy vegetable plant of the Brassicaceae family with high nutritional value and prospects for organic cultivation. The research was conducted from November 2023 to January 2024 aimed to determine the influence of liquid organic fertilizer application on the growth and yield of kale plants. The design used was a Completely Randomized Design (CRD) Non-Factorial. The treatments consisted of 5 types of various fertilizers repeated 4 times, with 12 plants per treatment. The treatments in this study were types of fertilizers, including: P0: Control (no Liquid Organic Fertilizer applied) P1: Rabbit Urine Liquid Organic Fertilizer P2: Leachate Liquid Organic Fertilizer P3: Coconut Water Liquid Organic Fertilizer P4: Biosaka (Bio Elisator). The results showed that rabbit urine liquid organic fertilizer (POC) showed a significant effect on all observed parameters. The best plant height resulted in 33.13 cm. Rabbit urine liquid organic fertilizer also showed the highest leaf count with 12.69 leaves compared to other varieties such as coconut water liquid organic fertilizer which showed a leaf count of 9.58 leaves. The best stem diameter was obtained with an average of 8.32 mm in the application of rabbit urine liquid organic fertilizer. The wet weight and dry weight of the harvested kale also showed the highest average weight of 2.22 kg and an average dry weight compared to the results of other liquid organic fertilizer applications, which was 2.15 kg. The wet weight and dry weight of the roots showed the highest averages, which were 2.11 grams and 2.00 grams respectively compared to other varieties  Key-words: kale; liquid organic fertilizer (LOF); urine; rabbit